The Relationship between Vocabulary Mastery and Speaking Fluency among Reflective and Impulsive Learners - Sultanova Sevara; Muhammad Yunus (Educazione: Journal of Education and Learning, 2025)
Indonesian learners of English consistently score lower in speaking than in reading or writing, a pattern the 2025 EF English Proficiency Index confirms at the national level. This study examines why by testing the relationship between vocabulary mastery and speaking fluency, and by asking whether that relationship holds equally for learners who process information deliberately and learners who process it rapidly. 20 eleventh-grade students at a senior high school in Malang completed a 20-item vocabulary test, a two-minute monologue scored against a fluency rubric, and a cognitive style questionnaire that classified 13 students as reflective and 7 as impulsive. Pearson correlation established a very strong association between vocabulary mastery and speaking fluency across the full sample (r = 0.947, p < 0.05), with vocabulary accounting for roughly 90 percent of the variance in fluency scores. Fisher's r-to-z transformation then compared the two subgroups and found no significant difference between them (Z = −0.280 against a critical value of ±1.96). Cognitive style did shape attainment, since impulsive learners scored higher on both vocabulary (70.00 against 59.23) and fluency (51.43 against 45.38), yet it left the conversion mechanism untouched. The finding separates two questions the literature has treated as one. Style governs how much lexical resource a learner accumulates. It does not govern how efficiently that resource becomes speech. Vocabulary instruction therefore requires no differentiation by cognitive style, because a word learned by a reflective student and a word learned by an impulsive student yield fluency at the same rate.